Effects of antenatal corticosteroids on neonatal outcomes in twin and singleton pregnancies: a Korean national cohort study. Issue 1 (23rd January 2023) - Bae, Seong Phil; Hahn, Won-Ho; Park, Suyeon; Jung, Young Hwa; Park, Jee Yoon; Oh, Kyung Joon; Choi, Chang Won
Abstract : Objective: To investigate whether effects of antenatal corticosteroids on neonatal outcomes in preterm infants with very low birth weight were different by plurality. Design: Nationwide prospective cohort study. Patients: Twins and singletons with very low birth weight (<1500 g) who were born between 23 +0 and 33 +6 weeks of gestation and registered in the Korean Neonatal Network from January 2014 to December 2019. Main outcome measures: Morbidity and mortality before discharge from neonatal intensive care unit. Results: Among a total of 9531 preterm infants with very low birth weight, there were 2364 (24.8%) twins and 7167 (75.2%) singletons. While 83.9% of singletons were exposed to at least one dose of antenatal corticosteroids, so were 87.9% of twins. Interaction analysis demonstrated that there was no significant difference in the effect of antenatal corticosteroids on morbidities or mortality between twins and singletons in either gestational age group (23–28 weeks or 29–33 weeks). Antenatal corticosteroids significantly decreased the risk of surfactant use (adjusted relative risk (aRR): 0.972 (95% CI: 0.961 to 0.984)), high-grade intraventricular haemorrhage (aRR: 0.621 (95% CI: 0.487 to 0.794)), periventricular leucomalacia (aRR: 0.728 (95% CI: 0.556 to 0.954)) and mortality (aRR: 0.758 (95% CI: 0.679 to 0.846)) in the gestational age group of 23–28 weeks. In the gestational age group of 29–33 weeks, antenatal corticosteroids significantly decreased the risk of surfactant use (aRR: 0.914 (95% CI: 0.862 to 0.970)) and mortality (aRR: 0.409 (95% CI: 0.269 to 0.624)) but increased the risk of sepsis (aRR: 1.416 (95% CI: 1.018 to 1.969)). Conclusion: This study demonstrates that effect of antenatal corticosteroids on neonatal outcomes of preterm infants with very low birth weight does not differ significantly by plurality (twin or singleton pregnancy).